Qualitative and psychometric evaluation of the PROMIS®-Fatigue SF-7a scale to assess fatigue in patients with moderately to severely active inflammatory bowel disease - Brian G. Feagan; William J. Sandborn; Bruce E. Sands; Yan Liu; Marion Vetter; Susan D. Mathias; Kuan-Hsiang Gary Huang; Jewel Johanns; Matthew Germinaro; Chenglong Han (SpringerOpen, 2023)
Abstract Background This study evaluated the content validity and psychometric properties of the Patient-Reported Outcomes Measurement Information System® (PROMIS)-Fatigue Short Form 7a (SF-7a) v1.0 scale to determine its suitability in clinical trials to assess fatigue in patients with moderately to severely active Crohn's disease (CD) and ulcerative colitis (UC). Methods A qualitative interview assessed patients' experience living with CD (N = 20) and UC (N = 19). The contents of the SF-7a scale were cognitively debriefed to evaluate content validity. A psychometric evaluation was performed using data from clinical trials of patients with CD (N = 360) and UC (N = 214). Correlations with Inflammatory Bowel Disease Questionnaire (IBDQ), Crohn's Disease Activity Index (CDAI; CD only), and Mayo score (UC only) determined validity. The Patient Global Impression of Change (PGIC) was used to evaluate reliability and responsiveness to change. Using PGIC as an anchor, a preliminary threshold for clinically meaningful change was identified to define fatigue response in both CD and UC patients. Results All patients reported fatigue as a common symptom. Patients confirmed SF-7a items were relevant to assessing fatigue, instructions and response options were clear, and its 7-day recall period was appropriate. Higher SF-7a scores were associated with higher disease activity (CDAI and Mayo score) and lower health-related quality of life (IBDQ), confirming known groups validity. The correlation of the SF-7a scale was higher with fatigue-related items. (rs ≥ -0.70) than with items not directly associated with fatigue. Test-retest reliability was moderate to good (0.54-0.89) among patients with stable disease, and responsiveness to change in disease severity was demonstrated from baseline to Week 12. A ≥7point decrease was identified as a reasonable threshold to define clinically meaningful improvement. Conclusion The SF-7a scale is a valid, reliable, and sensitive measure of fatigue in patients with moderately to severely active IBD and can be used to evaluate treatment response.